Effects of Microwave Modification on the Swelling Properties of Pinus radiata Heartwood - Awoyemi, Lawrence (Indian Forester, 2004)
The heartwood of Pinus radiata is known to pose some difficulties in drying but however have the advantage of high dimensional stability. The use of microwave modification as a pre-treatment method has been found to overcome to some degree the low drying rate. However it is important to investigate the effects of this pre-drying method on the dimensional stability in order to ensure that the achievement of improved drying rate is not at the expense of dimensional stability. Microwave modification of Pinus radiata heartwood was therefore carried out to study its influence on the swelling properties. The modification process resulted in reductions in swelling properties. This is invariably due to the modification of the anatomical structures particularly the tracheids and the ray tissues. Therefore, the dimensional stability of Pinus radiata heartwood was not only retained but also improved after microwave modification.